"حركة نیاغارا" في الولایات المتحدة الامریكیة: مقدماتھا ، نشأتھا، ١٩١٠- وعوامل انھیارھا ١٨٩ (Journal of the College of Education for Women, 2019)
The Negro minority in the United States is associated with social injustice,political deprivation, and economic oppresion. Its members felt that they aresecond-class citizens, and that the acceptance of such status will lead to thecontinual oppresion of the Whites upon them. As a result, the educated communityadopted a process to put a framework to their opposition to the former's injustice.This organised framework is exemplified in the "Niagara Movement," which isregarded as the first national organisation for Negros. The topic of this study ischosen due to its historical and political significance.The study consists of an introduction and five sections. The first sectionaddresses the preliminaries and the factors of the Movement establishment. It alsodeals with the conditions of the Blacks, and the emergence of some of the leadersamong them, whether those who made negotiations with the Whites, or those whorejected the bad conditions of the Blacks and sought to change them throughestablishing the Movement. The second section studies the Movementestablishment conference, and the objectives to be achieved. While the third sectionexamines the Movement numerous activities and the most important factors of itsvulnerability. The fourth section includes the subjective and objective factors thatled to the the Movement collapse . The final section contains an assessment to theMovement that shows its pros and cons according to the analytical historicalmethod of research.